The impact of Consumer Price Index Numbers indices on inflation in Sulaymaniyah Governorate for the period 2009-2019 - Omar, Luqman Othman; Hasan , Nashida Ahmed (Zanco Journal of Human Sciences, 2021)
Consumer price index numbers is one of the most important indicators that reveal the true reality of the level of economic and social well-being of consumers, and governments use them to know the changes that occur in the prices of consumer goods and services as well as the changes that occur in inflation rates. So the research analyzing the impact of consumer price index numbers on Inflation in Sulaymaniyah Governorate for the period (2010-2019), and a number of conclusions were reached, perhaps the most important were: The prices of the grouped goods and services recorded an increase in their record number in the years following the first year of the study and until the year (2014). The prices of the grouped goods and services recorded a decrease in their index in the years following (2014) and until the last year of the study. A number of suggestions has been reached, the most important could be: - Work to meet the local demand for goods by encouraging and supporting national industries by focusing on industries of comparative advantage, such as: vegetable and fruit canning, dairy products, textiles and clothing. Develop plans aim to stimulating economic growth and correcting structural imbalances between aggregate supply and demand, by controlling high price levels and inflation. The effectiveness of strict financial policies should not be neglected, first of all the reducing government operating spending (despite a review of government operating spending after the financial crisis that faced the Kurdistan region economy) should not be overlooked in affecting the amount of liquidity, price levels, and thus inflation rates.